New Economy in Poland after the Systemic Transformation: Main Issues - Nycz, Grzegorz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
The article describes the progress of a new economy in reference to the development of research and development (R&D) sector, the shaping of the information society, the spread of information and communication technologies (ICT), and the innovativeness of enterprises. In the case of Poland, the distance to European and global leaders of R&D was connected with, among others, the difficulties of enterprises with gathering resources for technological modernizations. Apart from economic (financial) barriers, such as limited access to capital for innovation activities, Polish enterprises also met market obstacles, showing the need of additional encouragements for the suppliers and recipients of innovations. The search for the signs of the new economy draws attention to the gradual development of the ICT sector, growing funds supporting R&D, and a wider usage of Internet networks for the needs of enterprises. The challenges faced with the aid of a regulatory participation of the state included creation of bounds between science and enterprises, strengthening of business environment institutions, reforms of research and development units, among others. After the accession of Poland to European Union, the availability of EU funds became a significant factor of the development of a knowledge-based economy, which enabled also broader R&D investments. The limitations of a new economy in Poland included inventiveness and expenditures on innovative activities, among others, whose size still does not guarantee fast growth in those areas.